New Pharmacotherapeutic Approaches for Chronic Obstructive Pulmonary Disease - Calverley, Peter; Vlies, Ben (Seminars in Respiratory and Critical Care Medicine, 2015)
The last 5 years have seen a proliferation of data about the best way to treat chronic obstructive pulmonary disease (COPD). New long-acting inhaled β-agonist and antimuscarinic drugs have been developed as a once-daily inhaled corticosteroid. Studies have tested whether these agents are safe and effective alone or in combination. Alternative strategies to treatment including phosphodiesterase-4 inhibition and long-term antibiotic treatment have become reasonable alternatives to more established approaches, at least in terms of preventing COPD exacerbations. New data are beginning to define which patients benefit from which treatments and this will help us develop more appropriate treatment regimes. These topics are considered in this review which provides an overview of the latest data and some direction as to how these findings can be applied in practice.
Keywords: bronchodilator; long-acting β-agonist; long-acting antimuscarinic; inhaled corticosteroids; combination therapy; phosphodiesterase-4 inhibition; long-term antibiotics